Novel anodic aluminum oxide (AAO) nanoporous membrane for wearable hemodialysis device - Ajab Khan Kasi (2018)
In this paper a novel structure of AAO membrane is reported. The AAO membrane was fabricated from commercial grade impure aluminum sheet. The fabricated membrane has hexagonal structure and the nanopores appeared at the bottom of that honeycomb structure. The thickness of fabricated membrane is 42.5μm. The average diameter of upper layer pore is 350nm and average diameter of lower layer pore is 50nm. The nanopores inside the fabricated membrane are highly straight and perpendicular to the surface. This two layer AAO membrane will speed up the hemodialysis process. ©2010 IEEE.